Mediasi Biaya Keagenan pada Pengaruh Kebijakan Utang dan Kebijakan Dividen terhadap Nilai Perusahaan-perusahaan Sektor Barang Konsumen Primer yang Terdaftar dalam Indeks Idxnoncyc Bursa Efek Indonesia Periode 2018-2020 - Andesta, Celvin Rama; Iryanto, M. Budi Widiyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
The primary purpose of establishing a company is to maximize its value of the company. In that process, firm value is inseparable from agency problems caused by shareholders' and managers' different interests. Several mechanisms are expected to reduce agency problems, including debt and dividend policies. However, until now, the role of these two policies in solving agency problems is still inconsistent. This study aimed to determine how agency costs mediate debt and dividend policy on firm value. The fundamental theories to solve this research problem are agency and free cash flow theories. The object of this study is to the primary consumer goods sector companies listed on the IDXNONCYC index on the Indonesia Stock Exchange in the 2018-2020 period, with a total final sample of 25 companies or 75 units of analysis. The data analysis technique used in this study is the path coefficient test using SmartPLS 3.2.9. With this technic, the authors analyze the outer model test, inner model test, and the goodness of fit test. The outer model test with bootstrapping outer weights has an invalid indicator, namely the PBV indicator. Therefore this indicator needs to be eliminated. The goodness of fit states that the model is significant but has a weak model. This study found that debt and dividend policy positively affect firm value and negatively affect agency costs. Agency costs have a positive and significant effect on firm value. Agency costs have no mediation effect of debt and dividend policy on firm value.